L'amour éclaté et recomposé. Sur quelques particularités de la réécriture de Réjean Ducharme - Vurm, Petr (Romanica Silesiana)
The article examines the problem of rewriting and intertextuality in the texts of a Québecois writer, Réjean Ducharme. The author analyses Ducharme’s recurrent topic of courtly love in relation to rewriting and intertextuality, juxtaposing the author’s literary texts and his sculptures and paintings, created under the pseudonym of Roch Plante. The text shows the similarity between Ducharme’s literary activity and his artistic collages. Both consist in permanent deconstruction/recomposition of a plethora of literary references, an inomissible element of Ducharme’s creativity. Key words: Réjean Ducharme; Roch Plante; rewriting; intertextuality; deconstruction; courtly love; surrealism